DAIVAVYAPASHRAYA CHIKITSA– THE MYSTIC & SPIRITUAL HEALING - Shalini HE; Shreevathsa (International Journal of Ayurveda and Pharma Research, 2020)
The concept of Daivavyapashraya is the most neglected modality of treatment and many of the diseases are not getting cured from its root. If a holistic approach where all trividha chikitsa is adopted, success rate of the treatment can be increased. Knowingly or unknowingly Daivavyapashraya Chikitsa is being carried out in different parts of the country as a part of religious beliefs, but it’s beyond that and focuses on Spirituality. So documentation of such practices which are becoming extinct and a detailed study on Daivavyapashraya Chikitsa is essential. Here, In this article an attempt has been made to analyse the concept of Daivavyapashrayachikitsa and is presented as follows: 1. The concept of Daiva 2.References in Samhitas 3.Traditional practices 4.Survey of various centres 5.Science behind the Mystic & Spiritual healing (Daivavyapashrayachikitsa).